Heart rate deflection point as an alternative to determining the anaerobic threshold in dyslipidaemic patients - Rochelle Rocha Costa; Thais Reichert; Bruna Machado Barroso; Vitória de Mello Bones da Rocha; Artur Avelino Birk Preissler; Éder Santiago; Eli Gonçalves Junior; Danielle Girolometto Fracalossi; Rodrigo Sudatti Delevatti; Luiz Fernando Martins Kruel (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: The aim of the present study was to verify the agreement between the ventilatory method (VT) and the alternative method of heart rate deflection point (HRDP) in determining the anaerobic threshold (AT) during incremental treadmill test in dyslipidaemic patients. Methods: Twenty-seven dyslipidaemic patients (61.50 ± 10.46 years) performed an incremental treadmill test, in which the AT was determined using both methods. Bland-Altman statistics was adopted in order to verify the agreement between the methods. Results: Agreement in AT determination between the VT and HRDP methods was observed (p < 0.05) for heart rate (138.00 ± 23.80 and 136.26 ± 22.18 bpm, respectively), oxygen uptake (31.00 ± 10.33 and 31.00 ± 11.17 ml.kg−1.min−1), and treadmill velocity (7.67 ± 1.71 km.h-1and 8.00 ± 1.75 km.h-1). Conclusion: Our results suggest that the HRDP method can be adopted for the determination of the AT in dyslipidaemic patients, showing agreement with the VT method.